2018
DOI: 10.1007/s00213-018-4849-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of lisdexamfetamine and D-amphetamine on social cognition and cognitive performance in a placebo-controlled study in healthy subjects

Abstract: The study was registered at ClinicalTrials.gov (NCT02668926).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 85 publications
2
28
1
Order By: Relevance
“…The absence of drug effects on the impulsivity measures was in line with expectations and previous studies with amphetamine, MDMA and cocaine (Bosker et al 2010; de Wit et al 2000; de Wit et al 2002; Dolder et al 2018; Kuypers et al 2007; Schmidt et al 2017). The average scores during drug and placebo conditions were also comparable to those found in previous drug studies by our group using the same paradigms (e.g., (Kuypers et al 2007; van Wel et al 2012).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The absence of drug effects on the impulsivity measures was in line with expectations and previous studies with amphetamine, MDMA and cocaine (Bosker et al 2010; de Wit et al 2000; de Wit et al 2002; Dolder et al 2018; Kuypers et al 2007; Schmidt et al 2017). The average scores during drug and placebo conditions were also comparable to those found in previous drug studies by our group using the same paradigms (e.g., (Kuypers et al 2007; van Wel et al 2012).…”
Section: Discussionsupporting
confidence: 89%
“…In general, it has been shown that amphetamine (10–40 mg) does not affect impulsive action (Dolder et al 2018), though when it does, an enhancing effect was found only in people who either performed badly at baseline (de Wit et al 2000; de Wit et al 2002) or when presented with complex stimuli (Fillmore et al 2003). Likewise, studies with MDMA have shown that in doses ranging from 25 to 125 mg, MDMA either leads to improvement of behavioral inhibition or induces no change (Bosker et al 2010; Kuypers et al 2007; Schmidt et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that MDMA plasma levels correlated positively with emotional empathy, whereas amphetamine plasma levels correlated negatively with cognitive performance (Dolder et al, ; Kuypers et al, ). Nonetheless, we acknowledge that the sample size might have been too small and thus underpowered to exclude effects of 4‐FA on emotional empathy because studies documenting effects of stimulants or empathogens on emotional empathy were larger (Dolder, Strajhar, Vizeli, Odermatt, & Liechti, ; Hysek et al, ; Kuypers et al, ). Future research could address these issues and test whether 4‐FA really induces a narrowing of attention and differentially affects emotion recognition dependent on salience of the cues and acute exposure to 4‐FA.…”
Section: Discussionmentioning
confidence: 96%
“…Impairment of social cognition by alcohol, for example, was attributed to a narrowing of attention, decreasing the influence of peripheral information, only leaving room for highly salient cues to attract attention (Pedersen, Aviles, Ito, Miller, & Pollock, ). 4‐FA was shown to improve tracking performance—the primary task in a divided attention task—without interfering with the secondary task—the detection of salient peripheral cues (de Sousa Fernandes Perna et al, ); this could be an indication of tunnel vision, a phenomenon which has been suggested to occur after D‐amphetamine (0.42 mg/kg; Silber, Croft, Papafotiou, & Stough, ), at a dose which is lower than the dose (40 mg) that caused improvement of emotional empathy (Dolder et al, ). In addition, although 4‐FA serum levels were not related to the reduction in cognitive empathy, acute exposure to 4‐FA could play a role in these effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation